Modified Space Vector Pulse Width Modulation for Three-Phase High Voltage Gain Switched-Inductor Split-Source Inverter - Mohammad Salehizadeh; Seyed Hamid Montazeri; Jafar Milimonfared; Hasan Rastegar (AUT Journal of Electrical Engineering)
Renewable energy sources, such as photovoltaic (PV) and fuel cells, have been given attention during the latest decades due to the limitations of non-renewable sources. Therefore, it is essential to improve the structure of voltage source inverters (VSIs) to increase their voltage gain in these applications. The split-source inverter (SSI) is a single-stage topology that uses the same number of power switches and switching states as VSI with boosting capability and the continuous input current. Three-phase switched-inductor SSI (SI-SSI) consists of two equal inductors, six diodes, one capacitor, and the bridge structure. This topology increases the voltage gain of conventional SSI. On the other hand, the modulation scheme impacts the inverters' performance. Space vector pulse width modulation (SVPWM) operates more efficiently than the third-harmonic injection pulse width modulation (THIPWM) and sinusoidal pulse width modulation (SPWM). However, varying the duty cycle of charging the inductors in each switching cycle increases the low-frequency ripples on the DC side of the inverter. To overcome the mentioned drawback in SVPWM, the modified SVPWM has been proposed. In the modified SVPWM, the interval corresponding to zero states is redistributed to charge both inductors of SI-SSI with similar constant duty cycles. Thus, the low-frequency components on the inductors' current and capacitor voltage are decreased without affecting the active states. The operation of three-phase SI-SSI with SPWM, THIPWM, traditional SVPWM, and modified SVPWM is investigated and simulated by MATLAB/Simulink.